Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan MIT App Inventor Pada Materi Statistika Siswa Kelas VIII SMP N 19 Kota Kupang - Silvana Yumalen Lima; Christine K. Ekowati; Imelda Hendriani Eku Rimo (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2021)
Inventor In Statistick Materials For Class VIII Students Of SMP N 19 Kota Kupang aims to produce products in the form of Android application-based learning media using MITT App Inventor In Statistick Materials For Class VIII Students Of SMP N 19 Kota Kupang which includes valid, practical, and effective aspects. The method used in this study is the Research and Development (R&D) method and the model used in the development of this android application-based learning media is the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. Data collection techniques and instruments used were interviews, questionnaires and tests. Data analysis techniques used are validity analysis techniques, practicality analysis techniques and effectiveness analysis techniques. The results showed that the android based learning media that had been developed was feasible to be used in learning Statistick Materials For Class VIII Students Of SMP N 19 Kota Kupang. The results of the feasibility of the learning media were obtained from the material expert assessment with an average of 4.0 and the media expert assessment of 4.36 so it was categorized as "very valid", the subject teacher's response with an average response result of 4.43 so it was included in the "very practical" category â€, as well as the results of student tests and student responses using learning media, the percentage of student graduation obtained is 80.65% so that it is included in the "very effective" category, while the average student response for this learning media is 4.44 so that based on test results and student responses, the learning media developed is very effective. Keywords: Development, Android-based Learning Media, Statistics